Variabilidade física, qualidade fisiológica, morfobiometria e análise cariotípica de crateva tapia L. - Silva, Rosemere dos Santos (2021)
The species Crateva tapia L., known as trapiá is a fruit tree that occurs in several forest formations, which has medicinal and landscape potential, recommended for the recovery of degraded areas and for feeding animals. Given the above, the objective was to study the physical variability, physiological quality, morphobiometry of fruits, seeds, seedlings and young plants and the karyotype characterization of the species C. tapia. The experiments were carried out in the Seed Analysis and Plant Cytogenetics Laboratories belonging to the Agricultural Sciences Center of the Federal University of Paraíba. Thus, in experiment I, only intact fruits were analyzed, totaling eight matrix trees evaluated for size, width, mass and number of seeds per fruit. Length, diameter and thickness of seeds from fifteen matrix trees were also evaluated. The physiological quality through the variables of germination and vigor was determined from 100 seeds of each of the fifteen matrix trees, both in a controlled environment and in the field. In experiment II, 100 fruits from eight matrix trees were measured for length, width, mass and number of seeds per fruit and 100 seeds from this lot were evaluated for size and fresh mass. The morphological description of the fruits was through observations on the external and internal aspects of the pericarp, peel consistency, color, shine, shape and dehiscence, while the consistency, color, texture, shape, hilum and embryo were observed in the morphology of the seeds. The seed water absorption curve was also evaluated for 216 hours at different temperatures, concomitantly with this test, the germination test was carried out under the same conditions, from which the observations and records of primary root protrusion until the appearance of the first pair started. of protophile and the young plant was followed from emergence to the third pair of eophyll and cotyledon senescence. In experiment III, the existence of intraspecific karyotype variations in different populations of C. tapia was analyzed based on the chromosome number and the distribution of heterochromatic bands using double staining with CMA/DAPI. In addition, meiotic cells were analyzed to identify Bs chromosomes and fluorescent in situ hybridization to determine the distribution of rDNA sites and confirm the occurrence of satellites or structural rearrangements. Quantitative data were submitted to descriptive and variance analysis by the F test. Among the fruits and seeds, there was variability in the biometric and physiological characteristics, whose fruits and seeds varied in size and fresh mass. The seeds are reniform, with an imbricate aspect, rigid integument, brown color and well developed hilum, and the embryo is cotyledonous and of incomplete morphology. Water absorption follows the triphasic pattern, with root protrusion occurring on the fourth day, epigeal-phanerocotyledon germination, the seedling has hypocotyl and herbaceous cotyledons, trifoliate compound leaf, the young plant has woody stem, alternating eophylls and there was the development of many abnormalities during the test, whose ideal temperature was 30 °C. In the study of cytogenetics, individuals with variation in the heterochromatin pattern composed of CMA+/DAPI– bands located in the terminal or proximal region were observed. Meiotic cell analysis showed no irregularities in meiosis, with 13 bivalent chromosomes being observed. The rDNA distribution showed the occurrence of two 5S sites in the proximal region and two 35S sites in the subterminal region, without evidence of structural rearrangements.